The Market Reaction to Firms’ ESG Disclosures: Does Audit Quality Matter? - Mulyadi Noto Soetardjo; Viochica Verawati (Universitas Pelita Harapan, 2024)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) Disclosure on capital market reaction, in this case, the Firm Value. Also, this study examines whether the relationship between ESG Disclosure and Firm Value is influenced by the moderating effect of audit quality. This study regresses three primary variables: Firm Value (measured using Price to Book Value), ESG Disclosure (measured based on the ESG Disclosure Score by BGK Foundation), and Audit Quality (is dummy variable with 1 for good audit quality). Using the purposive sampling method this study utilizes 202 firm-years sample from non-financial sector companies for the period 2018-2021. The major finding reveals that ESG Disclosure has a negative effect on Firm Value. Related to the influence of moderating variables, this study finds that Audit Quality is able to strengthen the positive effect of ESG Disclosure on Firm Value or weaken the negative effect of ESG Disclosure on Firm Value. The implication of this study shows that Audit Quality plays a role in decision making process related to Firm Value and ESG Disclosure.